Small developing economies and the multilateral trading system : a Caribbean perspective - Bernal, Richard L. ([s.n.] [S.l.])
Argues that, despite the costs and difficulties, small states must remain engaged in the multilateral system in order to ensure that their specialised commercial interests are recognised and to protect their rights.